2008
DOI: 10.1016/j.cell.2008.09.054
|View full text |Cite
|
Sign up to set email alerts
|

The P. furiosus Mre11/Rad50 Complex Promotes 5′ Strand Resection at a DNA Double-Strand Break

Abstract: Summary The Mre11/Rad50 complex has been implicated in the early steps of DNA double-strand break (DSB) repair through homologous recombination in several organisms. However, the enzymatic properties of this complex are incompatible with the generation of 3’ single-stranded DNA for recombinase loading and strand exchange. In thermophilic archaea, the Mre11 and Rad50 genes cluster in an operon with genes encoding a helicase, HerA, and a 5’ to 3’ exonuclease, NurA, suggesting a common function. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
203
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(223 citation statements)
references
References 51 publications
19
203
1
Order By: Relevance
“…The yeast ortholog Mre11-Rad50-Xrs2 (MRX) cleaves the 5 0 strand approximately 15-25 nt from the DNA end in vitro in a reaction that requires ATP hydrolysis, Mre11's nuclease motif, and the Sae2/CtIP protein (Garcia et al, 2011;Cannavo & Cejka, 2014;Shibata et al, 2014). Endonucleolytic cleavage of DNA near the breaks has also been observed for both archaeal and bacterial homologs, and could play a role in deprotection of DNA ends in bacteriophage T4 recombination (Connelly et al, 2003;Hopkins & Paull, 2008;Almond et al, 2013). The precise mechanism of how ATP aids and regulates nucleolytic and structural functions in all of these reactions is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast ortholog Mre11-Rad50-Xrs2 (MRX) cleaves the 5 0 strand approximately 15-25 nt from the DNA end in vitro in a reaction that requires ATP hydrolysis, Mre11's nuclease motif, and the Sae2/CtIP protein (Garcia et al, 2011;Cannavo & Cejka, 2014;Shibata et al, 2014). Endonucleolytic cleavage of DNA near the breaks has also been observed for both archaeal and bacterial homologs, and could play a role in deprotection of DNA ends in bacteriophage T4 recombination (Connelly et al, 2003;Hopkins & Paull, 2008;Almond et al, 2013). The precise mechanism of how ATP aids and regulates nucleolytic and structural functions in all of these reactions is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with purified proteins have also shown that MR and MRN(X) complexes recruit long range exo/endonucleases and also help to block the inhibitory effects of Ku (5,6,34,48,49). Here, we found that MRN strongly promotes DNA resection by Exo1 in the presence of both Ku and DNA-PKcs in a dose-dependent manner (Fig.…”
Section: Mrn Overcomes Dna-pkcs Inhibition Of Exo1 Activity-mrmentioning
confidence: 99%
“…The canonical divalent cation for Mre11 is Mn 2ϩ , but recent work on Mre11 from Pfu and T4 indicate that Mg 2ϩ also supports nuclease activity (24,25). Interestingly, Mg 2ϩ appears to favor a potentially more physiologically relevant double-stranded DNA endonuclease activity that produces a 3Ј single-stranded DNA overhang that is an intermediate in the HR pathway (25).…”
mentioning
confidence: 99%